A inserção da agricultura familiar na constituição da cadeia do leite no município de Nossa Senhora da Glória/SE - Rodrigues, Sandra Andréa Souza (2015)
This study about family dairy farming in the municipality of Nossa Senhora da Glória analyzed the productive and social processes from the dynamics of supplier production of stock and from the allocation sociability to the market. In these terms, this research aimed to analyze the diversity of dairy production chain’s systems in the municipality of Nossa Senhora da Glória, in Sergipe state, in order to strengthen the comprehension of the importance about family farming in its insertion to a regional market, which benefits local development. This study is justified due to social and economics unfoldment as well as the organization of the rural space, the role of the institutionality and the social actors’ perception involved in this process. For this purpose, we started from a bibliographic research about the theme, followed by direct and indirect observation of the facts through field research, with application of surveys to the protagonists of this process, the dairy producers, as well as interviews and data collection with federal, state, municipal and institutional organs. The information obtained proved the stabilization of producers, mainly the family farmer, with dairy production as the only alternative for source of income, which generates working places in many sectors such as transportation of stock and in production and trading of derived products. This alimentary and agriculture activity has quintessentially a strong relation with the high sertão, located in the northwest of the state, especially in Nossa Senhora da Glória, due to the dominant historical process in the area portrayed as plaintiff of stock, in other words, in natura, which is currently remarked by an asymmetric chain, but that haven’t been characterized as a system yet, due to economic factors that determine procedures such as price, production time and the amount to be sold. The chain has been fragmented due to the disbelief of the actors under institutional inclusion, which would be a way of linear flow, eliminating the intermediaries’ action and the prominence of small factories that emerged as a strategy to consolidate dairy distribution, acting also as mediators to the local industries. Thereby, family farmers, inserted in the dairy production chain, strengthen increasingly a sociability network with the small factories substantiated on the guarantee of income, which has been concretized weekly, making them captive of trading channels that feed informal and formal market, in local and regional scales in Brazil’s northeast.